Gram-Scale Synthesis of (±)-Tylophorine - Masal, Dattatraya P.; Reddy, D. Srinivasa (Synlett, 2024)
We report a practical scalable synthesis of the natural product (±)-tylophorine by using an operationally simple protecting-group-free route from readily accessible starting materials. Synthesis of a cyclic N-acetyl diester compound through cyclization, followed by two key steps (decarboxylation and a Clemmensen reduction), provides access to the target molecule.
Keywords: gram-scale synthesis; tylophorine; alkaloids; decarboxylation; Clemmensen reduction